The Influence of Collective Leadership on Pastoral Ministry Effectiveness and Congregation Growth - Ponco Mujiono; Daniel Ari Wibowo (Jurnal Didaskalia, 2023)
Shepherding has been an ongoing task throughout the history of the Church of God on Earth. From the day of Pentecost (Acts 2) until the rapture of the Church (1 Thess. 4: 13-18), the Church of the Lord will continue to exist on Earth, necessitating the shepherding of the church's ministers. This study seeks to assess the extent of the influence of collective leadership on the effectiveness of pastoral Ministry and church growth. In this research, the independent variable is "collective leadership" as studies often focus on single leadership. This quantitative study aims to provide empirical insights into the impact of applying collective leadership, as outlined in Ephesians 4:11-16, on the effectiveness of pastoral care and church growth. The variables examined in this study include collective leadership in Gereja Kristen Perjanjian Baru 'Masa Depan Cerah' Surabaya as variable X, the effectiveness of pastoral care as variable Y1, and congregation growth as variable Y2. The author adopts quantitative research methods and statistical calculations to draw conclusions. The direct impact of collective leadership (X) on congregation growth (Y2) is evident from the significant p2 value of 0.717, as indicated by a t count of 11.072 with a significance level of 0.000 (p < 0.05). This suggests that collective leadership (X) has a direct and significant effect on congregation growth (Y2). The total influence includes both direct and indirect influences (p1 + (p2 + p3). The total influence of collective leadership (X) on congregation growth (Y2) when mediated through pastoral care (Y1) amounts to 0.662 + 0.825, resulting in a total influence of 1.487.